Efficacy of Patient-Specific Strategy: Catheter Ablation Strategy of Persistent Atrial Fibrillation Based on Morphological Repetitiveness by Periodicity and Similarity. (18th May 2021) - Lin, Chin-Yu; Lin, Yenn-Jiang; Lo, Men-Tzung; Chiang, Chia-Hsin; Chen, Yun-Yu; Kuo, Ling; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Chao, Tze-Fan; Chung, Fa-Po; Liao, Jo-Nan; et al.
Abstract : Supplemental Digital Content is available in the text.